(untitled) (Al-Mansour Journal, 2022)
This study aimed to investigate the effect on the quality of service and customer loyalty for hotels in the city of Oran, Algeria where he was preparing a questionnaire consisting of the first two dimensions for the dimensions of quality of service, and the second related to the loyalty of customers of the hotel and this for primary data collection. Has been relying on the sample probability class. Were also distributed 500 form. To be retrieval 345 form and the number of forms completed data that has been recovered amounted to 320 form. Reaching response rate of 64%. And to identify the impact of the dimensions of service quality on customer loyalty has been the use of multiple regression analysis , the results showed a positive relationship between the two.